Evolusi rumah dan kehidupan keluarga - Fatimah Abdullah, (Universiti Kebangsaan Malaysia, 2009)
Family house is more than a physical structure. It is a symbol of life. Family house evolves as family moves from birth, maturity, adulthood and death; therefore house structure change according to the stages. Since social and cultural change occurs in urban and rural areas, so do family houses in both areas. Changes in family houses are not specific to it’s size but the internal and external structure change as well. This paper shall discuss evolution of the house which is very much related to changes in the family. The writer believes that theoretical perspectives on family and kinship were focused more on it’s social organization and discussion on “the house” from it’s physical and symbolic structure together with rules related to its social organizations is important as well. This article attempts to discuss the idea of family house which experience “life” and “death” as what happen to the family who lives in it and how social organizations and relations in a contemporary urban family is determine by it’s house structure. Discussion in this paper was based on studies on family done by the writer and other literatures on the family especially Malay families